Women home, excelled men : essays to enliven you - Gnanasekar, Hemalatha. 1965- (Delhi : Kalpaz, 2009)
Humorous essays.
Includes index.
Keywords: Gnanasekar, Hemalatha, -- 1965- -- Childhood and youth; Indic wit and humor (English); India -- Social life and customs -- Personal narratives